A case report of de novo missense FOXP1 mutation in a non‐Caucasian patient with global developmental delay and severe speech impairment. Issue 2 (24th November 2014) - Song, Hao; Makino, Yuka; Noguchi, Emiko; Arinami, Tadao
<x xml:space="preserve">Abstract</x> The FOXP protein family (FOXP1‐4) is a group of transcription factors that play important roles in embryological, immunological, hematological, and speech and language development. Here, we report FOXP1 de novo mutation and severe speech delay in an individual belonging to a non‐Caucasian population. <boxed-text content-type="graphic" id="ccr3167-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>